Retrospect of the Marketing Strategies and Services in a Chinese Pharmaceutical Company - Ditan, Carolina (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
The study was conducted to determine the effective marketing strategies in terms of promotion, product, pricing and place, and services in terms of availability, reliability, responsiveness, completeness and professionalism rendered of a Pharmaceutical Company in China as perceived by the two groups of respondents, employees and customers/clients. The four marketing strategies obtained a very effective descriptive rating by the employee and client-respondents. Among the four marketing strategies, Pricing gained an effective rating from employee-respondents and Place has a significant difference in the perceptions of the two groups of respondents. In terms of services rendered a very effective descriptive ratings were given by the employee-respondents; whereas, client-respondents only obtained an effective descriptive rating. Among the five services rendered, only professionalism was perceived as very effective and was tagged as no significant difference by the two groups of respondents. High relationship between the marketing strategies and services rendered by the Pharmaceutical Company to its clients in the obtained r value of 0.74 which means that the marketing strategies of employees directly affect the clients’ services. At 0.05 Alpha, it was concluded that if the marketing strategies of the employees improved, so as their services to the clients. It is recommended that a successful pharmaceutical company must build customer knowledge competence through improvement of the current processes that include customer data acquisition and data interpretation.